In-silico primer designing and validation of Bos taurus and Sus scrofa SET proto-oncogene for non-halal detection - Muhammadi, Fatimah Mustafawi; Solihah, Jumailatus; Hamdani, Anti Damayanti (Journal of Halal Science and Research, 2025)
The SET gene is part of the proto-oncogene family. Proto-oncogenes families are expressed in cell growth regulation, notably during embryogenesis, wound healing, liver regeneration, and mitotic stimulation by growth factors. While proto-oncogenes have been extensively studied for their role in cancer detection, their application in halal certification assessments remains minimal. Polymer Chain Reaction (PCR) has recently been an alternative method in species authentication due to its high accuracy, with primers being a critical component in determining the amplification process's success. Consequently, primers must be carefully and specifically designed. This study uses a bioinformatics approach to explore the potential of the SET proto-oncogene as a candidate primer for non-halal detection. SET proto-oncogene sequences from pig (Sus scrofa) and cattle (Bos taurus) were retrieved from the National Center for Biotechnology Information (NCBI) database and aligned using MEGA6 software to identify conserved regions suitable for primer design. The designed primers were tested through in-silico PCR and subsequently validated using conventional PCR. The results demonstrated that two primer pairs successfully produced amplicons with lengths of 1068 bp and 1231 bp in cattle and 1275 bp and 1222 bp in pigs, consistent with in-silico predictions.   Keywords: Halal, In-silico, Primer, Proto-oncogene, SET gene.